2019
DOI: 10.1038/s41598-019-38928-6
|View full text |Cite
|
Sign up to set email alerts
|

Early differentiation of long-standing persistent atrial fibrillation using the characteristics of fibrillatory waves in surface ECG multi-leads

Abstract: We characterized the f-waves in atrial fibrillation (AF) in the surface ECG by quantifying the amplitude, irregularity, and dominant rate of the f-waves in leads II, aVL, and V 1 , and investigated whether those parameters of the f-waves could discriminate long-standing persistent AF (LPeAF) from non-LPeAF. A total of 224 AF patients were enrolled: 112 with PAF (87 males), 48 with PeAF (38 males), and 64 with LPeAF (47 males). The f-waves in surface ECG leads V 1 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Low f-wave frequency can predict successful outcome in patient with persistent AF undergoing cardioversion (Bollmann et al, 2008 ) and high f-wave frequency predicts early AF recurrence (Bollmann et al, 2003 ). The f-wave frequency can increase with the progression of AF, and patients with persistent AF often have a higher f-wave frequency than patients with paroxysmal AF (Alcaraz et al, 2011 ; Park et al, 2019 ). Further, it has been shown that a low f-wave frequency is associated with spontaneous conversion of recent-onset AF (Choudhary et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Low f-wave frequency can predict successful outcome in patient with persistent AF undergoing cardioversion (Bollmann et al, 2008 ) and high f-wave frequency predicts early AF recurrence (Bollmann et al, 2003 ). The f-wave frequency can increase with the progression of AF, and patients with persistent AF often have a higher f-wave frequency than patients with paroxysmal AF (Alcaraz et al, 2011 ; Park et al, 2019 ). Further, it has been shown that a low f-wave frequency is associated with spontaneous conversion of recent-onset AF (Choudhary et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…This finding is not completely surprising due to two reasons. On the one hand, lead II can capture information from both right and left atria, because it is aligned with the interatrial septum [14]. In this way, f -waves in this lead could reflect more globally atrial activity and its organization.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to extract features from atrial activity either an isolated f-wave or ECG excerpt excluding QRS complex (e.g TQ interval) are used. To get an isolated f-wave or ECG free from QRS complex, QRS cancellation is a common preliminary step [88]. Popular methods of QRS cancellation include direct suppression of QRS, average beat subtraction (ABS) [89], [90], use of filters (e.g, bandpass filter, adaptive filter) [91], spatiotemporal QRS cancellation, blind source separation, independent component analysis, and principal component analysis.…”
Section: Features Extractionmentioning
confidence: 99%